Online-to-Offline (O2O) E-Commerce Adoption Using Technology Acceptance Model 3 (TAM 3): The Case of GrabKios - Elwin Jusuf Togatorop; Mardiana Purwaningsih (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2025)
The rapid growth of digital technology has streamlined workflows and accelerated information exchange. However, it has also introduced risks such as data theft and online fraud, which make people hesitant to engage in online transactions. To address these concerns, platforms such as GrabKios have introduced online-to-offline (O2O) solutions, enabling users to order goods online through local agents and pay in cash. While GrabKios shows strong potential, its adoption remains limited, particularly among small kiosk (warung) owners who face difficulties navigating the app. This study examines the factors influencing the use of GrabKios by applying the Technology Acceptance Model 3 (TAM3). A total of 108 respondents participated in the survey. The findings indicate that perceived usefulness significantly influences behavioural intention; however, adoption does not occur unless the app is user-friendly. Usability issues, therefore, remain a significant barrier to broader adoption. These results underscore the importance of intuitive interface design and user-friendly features in promoting the broader adoption of O2O e-commerce applications. This research contributes to the field by extending the application of TAM3 in the O2O context, which remains underexplored. It offers practical implications for developers in designing simpler and more accessible digital platforms.